A comparative evaluation of vertical marginal fit of provisional crowns fabricated by computer-aided design/computer-aided manufacturing technique and direct (intraoral technique) and flexural strength of the materials: An in vitro study - Ishita Dureja; Bhupender Yadav; Puja Malhotra; Nupur Dabas; Akshay Bhargava; Ripul Pahwa (Wolters Kluwer Medknow Publications, 2018)
Background: With the advent of new provisional crown materials, it has become imperative to evaluate their marginal fit and strength to select the ideal provisional crown material. Aim: The purpose of this in vitro study was to evaluate and compare the vertical marginal fit and flexural strength of provisional crowns prepared using computer-aided design-computer-aided manufacturing (CAD-CAM) temporary material versus those fabricated using bis-acrylic composite-based autopolymerizing resin material. Materials and Methods: Eighty samples were divided into two equal Groups (I and II). Group I consisted of forty samples that were evaluated for flexural strength and Group II consisted of forty samples that were evaluated for their vertical marginal fit. Group I was subdivided as Group IA, i.e., bis-acrylic composite-based autopolymerizing resin material (Protemp™ 4) blocks and Group IB, i.e., CAD/CAM provisional material blocks. Similarly, Group II was subdivided as Group IIA, i.e., bis-acrylic composite-based autopolymerizing resin material (Protemp™ 4) crowns and Group IIB, i.e., CAD/CAM provisional material crowns. Marginal adaptation was evaluated using stereomicroscope and image analyzing software to measure the amount of marginal gap. For flexural strength, all specimens were subjected to a standard compression load in the universal testing machine until fracture occurred. Data were analyzed using Student's t-test (P = 0.001). Results: CAD/CAM provisional crowns showed better marginal adaptation (34.34 μm) as compared to bis-acrylic composite-based autopolymerizing resin material (Protemp™ 4) crowns (63.42 μm) (P < 0.001). The flexural strength of CAD/CAM blocks (94.06 megapascals [MPa]) was not statistically different from bis-acrylic composite-based autopolymerizing resin material (Protemp™ 4) blocks (101.41 MPa) (P > 0.001). Conclusion: Protemp™ 4 and CAD/CAM provisional materials have comparable flexural strength. However, the marginal fit of temporary crowns fabricated by CAD/CAM was found to be superior to the ones fabricated using bis-acrylic composite-based autopolymerizing resin material (Protemp™ 4).